Application of Encapsulation Technology to Improve the Growth Rate of New Zealand Black-Footed Abalone (Haliotis iris) - Masoomi Dezfooli, Seyedehsara (Auckland University of Technology, 2020)
Abalone is a marine gastropod mollusc belonging to the family Haliotidae. Black-footed abalone, (Haliotis iris) bred and harvested uniquely in New Zealand, has a high market demand due to its high quality and chemical-free farming process. However, the slow growth rate of abalone has limited its sustainable production. Many studies have shown that probiotics can improve the growth rate and health of abalone. However, effective delivery of probiotics to farmed abalone has remained a challenge. Conventional probiotic delivery methods through culture water or as feed supplements may lead to environmental contamination, loss of activity and insufficient dosages. This thesis aims to develop a new probiotic delivery system to enhance health and growth rate of black-footed abalone. A literature review was conducted to analyse the application of encapsulation technology in developing novel delivery methods for various bioactives including probiotics, nutrients and immunostimulants to farmed aquatic species (Chapter 2). A pre-formulation study was performed to confirm the beneficial characteristics of probiotics previously isolated from healthy abalone. The three bacterial species namely Exiguobacterium sp., Enterococcus sp. and Vibrio sp. were characterised and their abilities to help in feed digestion were confirmed (Chapter 3). The probiotic bacteria were then encapsulated in chitosan and alginate-based microparticles. The efficiency of microparticles in encapsulating the probiotics and creating a pH-dependent release in the simulated gastric and intestinal fluids of abalone were demonstrated. The developed microparticles displayed floating behaviour in seawater, hence, they were immobilised in alginate beads to improve their accessibility to abalone. Fluorescence microscopy suggested minimum leach of the encapsulated bacteria into seawater followed by the successful delivery of microparticles into abalone’s gastrointestinal tract (GIT). The high load of probiotic bacteria in the GIT of probiotic-fed animals illustrated the potential of the developed microparticles as new carriers for oral administration of probiotics to abalone (Chapter 4). To simplify the production process of encapsulated probiotics, an extrusion method was utilised to develop chitosan-coated alginate beads instead of microparticles. Encapsulated probiotic beads with desired properties including spherical shape, fast sinking, high palatability, high stability and minimum release in seawater were obtained. The tracking experiment using fluorescent-labelled probiotics confirmed the successful delivery of the encapsulated probiotics into the GIT of probiotic-fed abalone (Chapter 5). The efficiency of the developed beads to improve the health and growth of abalone were assessed by performing a two-month feeding trial. Four different dietary treatments including 1) conventional feed, 2) feed sprayed with probiotic culture, 3) combination of encapsulated probiotics and conventional feed, and 4) encapsulated probiotics containing nutrients were used to feed juvenile black-footed abalone. Diet 4 successfully improved growth performance, feed utilisation, feed conversion rate and reduced feed wastage. Flow cytometric analysis revealed a lower level of oxidative stress associated with diet 4 compared to the other diets. Metabolomics analysis on abalone foot muscle further revealed that abalone fed with diet 4 differentially regulated 31 metabolites mostly composed of free amino acids which may indicate a better delivery of feed. Therefore, chitosan-coated alginate beads can be considered as an effective probiotics and nutrients delivery method to black-footed abalone capable of increasing abalone health and growth performance while minimising feed wastage, environmental impact and hence feed cost (Chapter 6). In conclusion, an encapsulated system was developed to deliver viable probiotics as well as nutrients to farmed black-footed abalone. The developed system was capable of protecting its contents in seawater, delivering them to the GIT of abalone, enhancing health and growth and achieving high consumption rates as well as minimising wastage. The encapsulated delivery system developed in this thesis can be scaled up for commercial production, and adaptation of such technologies could help to further develop abalone aquaculture industry in New Zealand and abroad in a sustainable manner.
Keywords: Encapsulation; Abalone; Aquaculture; Emulsion; Probiotics